Efektifitas dan Kesinambungan Pembangunan Taman Tematik Terhadap Kesejahteraan Masyarakat di Kota Jambi - Ridwan Ridwan; Anggin Maria; Mulia Jaya (Universitas Muara Bungo, 2023)
This research is directed at describing the Jambi City Government's strategy in improving the function of the Youth Park to support the welfare of the surrounding community. Then identify what obstacles are faced in improving the function of youth parks as supporting the welfare of the surrounding community. Next, it explains the Jambi City government's efforts to overcome obstacles in improving the function of the Youth Park in supporting the welfare of the surrounding community. The method in this research is descriptive qualitative. The development of tourist attractions must continue to be carried out by means of innovation, the development of management of facilities and facilities must continue to be carried out in order to provide comfort for tourists who come to this youth park object. Human resource development by the Government must continue to be carried out periodically. Especially for the public and visitors so that there are no more criminal acts that can damage the beauty of the youth park.